Effects of High-Speed Power Training on Muscle Performance and Braking Speed in Older Adults - Stephen P. Sayers; Kyle Gibson (Journal of Aging Research)
We examined whether high-speed power training (HSPT) improved muscle performance and braking speed using a driving simulator. 72 older adults (22 m, 50 f; age = 70.6 ± 7.3 yrs) were randomized to HSPT at 40% one-repetition maximum (1RM) (HSPT: n=25; 3 sets of 12–14 repetitions), slow-speed strength training at 80%1RM (SSST: n=25; 3 sets of 8–10 repetitions), or control (CON: n=22; stretching) 3 times/week for 12 weeks. Leg press and knee extension peak power, peak power velocity, peak power force/torque, and braking speed were obtained at baseline and 12 weeks. HSPT increased peak power and peak power velocity across a range of external resistances (40–90% 1RM; P<0.05) and improved braking speed (P<0.05). Work was similar between groups, but perceived exertion was lower in HSPT (P<0.05). Thus, the less strenuous HSPT exerted a broader training effect and improved braking speed compared to SSST.